What can single photons do what lasers cannot do?. (24th September 2019) - Rezai, Mohammad; Sperling, Jan; Gerhardt, Ilja
Abstract: Coherence forms the foundation of quantum information processing and roots its bases in effects such as quantum interference and entanglement. In our classically perceived life, interference is a familiar notion, but what makes this phenomenon 'quantum' is a challenging task to be quantitatively verified. In this contribution, we experimentally implement quantum interference and investigate the impact of different origins of an interference pattern by characterizing correlations obtained with distinct light sources, namely single photons and laser light. We present the correlation measurements on a general class of linear optical gates in a uniform format. Consequently, this modeling provides a precise characterization of different photonic sources. Specifically, we demonstrate how an interference pattern can be uniquely decomposed into a classical and quantum part. By extension, our approach renders it possible to perform a comprehensive analysis of the wave-particle duality in quantum-optical interference experiments.